2004
DOI: 10.1007/s10152-004-0199-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability in abundance and biomass of ciliates and copepods in the eutrophicated part of Kaštela Bay (Middle Adriatic Sea)

Abstract: Seasonal variations in abundance and carbon biomass of ciliated protozoa and micrometazoa were studied from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 48 publications
3
31
0
Order By: Relevance
“…Average abundances of the ciliate dominated protozoan assemblage in the study area were low compared to highly productive Adriatic bays (Revelante and Gilmartin 1983;Bojanić 2001;Bojanić et al 2005), showing more similarity to those recorded in the mesotrophic channel areas (Bojanić 2002). Non-loricate ciliates (NLC) seemed to be regulated by salinity, rather than temperature.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Average abundances of the ciliate dominated protozoan assemblage in the study area were low compared to highly productive Adriatic bays (Revelante and Gilmartin 1983;Bojanić 2001;Bojanić et al 2005), showing more similarity to those recorded in the mesotrophic channel areas (Bojanić 2002). Non-loricate ciliates (NLC) seemed to be regulated by salinity, rather than temperature.…”
Section: Discussionmentioning
confidence: 75%
“…The samples were preserved in 2.5% formaldehyde-seawater solution, previously buffered with CaCO 3 , since Lugol's solution stains detritus and would reduce visibility (Fonda-Umani and Beran 2003). Preparation of the samples for the microscopic analysis was performed as described in Bojanić et al (2005). Counting and species identification were performed with an inverted microscope at 100· and 400· magnifications.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…NLC and TIN compositions, as well as temporal and vertical fluctuations in density and biomass, have been presented in detail previously (Bojanić et al, 2005).…”
Section: Ciliated Protozoamentioning
confidence: 99%
“…The effect of micrometazoans on phytoplankton could also be indirect, via trophic cascade. Earlier investigation in the adjacent Kaštela Bay suggested that predator activities of small copepods are primarily directed towards nonloricate ciliates (Bojanić et al, 2005), which in turn may increase phytoplankton biomass through the suppression of direct grazers. This was confirmed by the positive and significant correlation between overall phytoplankton abundance and small metazoans (mainly copepod nauplii: Spearman R=0.502 P<0.01).…”
Section: Discussionmentioning
confidence: 99%
“…The samples were preserved in a 2.5% formaldehyde-seawater solution, previously buffered with CaCO 3 , since Lugol's solution stains the detritus that can be abundant in this area and would thus reduce visibility (Fonda-Umani & Beran, 2003). Preparation of the samples for microscopic analysis was performed as described in detail in Bojanić et al (2005). Counting and species identification were carried out using an inverted microscope (Olympus IMT-2) at 100x and 400x magnification.…”
Section: Sampling and Measurement Methodsmentioning
confidence: 99%